Training in creating promotional media designs and financial management for MSMEs in Salo Palai Village, Kutai Kartanegara - Dita Andansari; Amiril Azizah; Ratna Wulaningrum; Dwi Cahyadi; Zainal Arifin; Ahyar Muhammad Diah; Budi Nugroho; Dedy Irawan (Community Empowerment, 2023)
Salo Palai Village is experiencing significant growth in new Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector. However, management practices are still conventional. Therefore, this community service aims to enhance the skills of MSMEs, especially in promotional media design and financial reporting. The activities involve lectures and hands-on practice. As a result of this training, all participants can now operate Corel Draw for promotional media design and are proficient in creating simple financial reports to monitor business performance.